The importance of considering resource's tasks when modeling healthcare services with discrete-event simulation: an approach using work sampling method. Issue 2 (1st May 2017) - Baril, C; Gascon, V; Miller, J; Bounhol, C
Abstract: Discrete event simulation (DES) is increasingly used to model and analyse healthcare systems processes. Unlike the manufacturing industry, healthcare personnel benefits from a professional independence allowing them to choose the next task to accomplish. Because of this characteristic modelling healthcare systems with DES is more complex. This paper introduces a work sampling method to model nurses' direct and indirect tasks in a haematology-oncology clinic. We show how this method helps to obtain a more realistic DES model.